Pengaturan Organisasi Kemasyarakatan Sebagai Pelaksana Dalam Pengadaan Barang/Jasa Pemerintah Di Indonesia - Kadek Cahya Susila Wibawa (Administrative Law and Governance Journal, 2020)
The aim of this study is to understand the politics of procurement of government goods / services through self-management based on Presidential Regulation Number 16 Year 2018 concerning Procurement of Government’s Goods/Services by focusing on Type III Self-Management as collaboration between the Government and social organizations.The results of the study show that the existence and dynamics of the development of social organizations and changes in the government system gave rise to a new paradigm for the organization of social organizations in the life of the community, nation and state especially in the procurement of goods/services. Law and politics play a role as social subsystems which are in the position where the degree of determination is balanced, so even though the law is a product of political decisions, but once the law is in force, political activity must obedient to the rule of law. Collaboration between the Government and Social Organizations generate the regulation of Type III Self-Management in Presidential Regulation Number 16 Year 2018 concerning Procurement of Government’s Goods/Services, in which the Perpres became a legal platform (providing legal certainty) for the Government to provide and give space to the public (in this case is the social organization) to be actively involved and participate in national development to realize national goals and ideals. Keywords      : Procurement of Government’s Goods/Services; Type III Self-Management, Social Organizations. Abstrak Tujuan dari penulisan ini adalah untuk memahami politik hukum pengadaan barang/jasa pemerintah melalui swakelola berdasarkan Peraturan Presiden RI Nomor 16 Tahun 2018 tentang Pengadaan Barang/Jasa Pemerintah, dengan lebih terfokus pada Swakelola Tipe III sebagai kolaborasi antara Pemerintah dengan organisasi kemasyarakatan. Hasil studi  menunjukkan bahwa eksistensi dan dinamika perkembangan organisasi kemasyarakatan dan perubahan sistem pemerintahan memunculkan sebuah paradigma baru bagi pengaturan organisasi kemasyarakatan dalam kehidupan bermasyarakat, berbangsa, dan bernegara khususnya dalam pengadaan barang/jasa. Hukum dan politik berperan sebagai subsistem kemasyarakatan yang berada pada posisi di mana derajat determinasinya seimbang sehingga meskipun hukum merupakan produk keputusan politik tetapi begitu hukum telah berlaku maka kegiatan politik harus tunduk terhadap aturan hukum. Kolaborasi antara Pemerintah dengan Organisasi Kemasyarakatan memunculkan adanya pengaturan mengenai Swakelola Tipe III dalam Peraturan Presiden RI Nomor 16 Tahun 2018 tentang Pengadaan Barang/Jasa Pemerintah di mana Perpres tersebut menjadi sebuah landasan hukum (memberikan kepastian hukum) bagi Pemerintah dalam menyediakan dan memberikan ruang kepada masyarakat (dalam hal ini adalah organisasi kemasyarakatan) untuk terlibat aktif dan berpartisipasi dalam pembangunan nasional untuk mewujudkan tujuan dan cita-cita nasional. Kata Kunci    : Pengadaan Barang/Jasa Pemerintah; Swakelola Tipe III; Organisasi Kemasyarakatan.